Physical dissection of the CCAAT/enhancer-binding protein α in regulating the mouse amelogenin gene - Xu, Yucheng; Zhou, Yan Larry; Erickson, Robin L.; MacDougald, Ormond A.; Snead, Malcolm L. (Biochemical and biophysical research communications, 2007)
The amelogenin gene is tightly regulated at the temporal and spatial level in accord with the developmental requirement for tooth formation. Previous studies have shown that CCAAT/enhancer-binding protein α (C/EBPα) is a transactivator of the mouse X-chromosomal amelogenin gene. C/EBPα contains four highly conserved regions (CR) named CR1, CR2, CR3, and CR4. Transient transfection assays showed that CR2 in isolation had an exceptional capacity to enhance transcription from the 2.3 kb mouse amelogenin promoter. The remaining conserved regions of C/EBPα, either in isolation or in selected combinations, were less effective in amelogenin transactivation than the full length C/EBPα. Msx2 has previously been shown to antagonize C/EBPα through protein–protein interactions with C/EBPα, and the carboxyl-terminus of Msx2 is required for protein–protein interactions. Co-immunoprecipitation analyses identified that the carboxyl-terminal domain (residues 218–359) of C/EBPα is required for the C/EBPα–Msx2 protein–protein interactions.